Safety and efficacy of non‐steroidal anti‐inflammatory drugs to reduce ileus after colorectal surgery. Issue 2 (9th October 2019) - ,
Abstract : Background: Ileus is common after elective colorectal surgery, and is associated with increased adverse events and prolonged hospital stay. The aim was to assess the role of non‐steroidal anti‐inflammatory drugs (NSAIDs) for reducing ileus after surgery. Methods: A prospective multicentre cohort study was delivered by an international, student‐ and trainee‐led collaborative group. Adult patients undergoing elective colorectal resection between January and April 2018 were included. The primary outcome was time to gastrointestinal recovery, measured using a composite measure of bowel function and tolerance to oral intake. The impact of NSAIDs was explored using Cox regression analyses, including the results of a centre‐specific survey of compliance to enhanced recovery principles. Secondary safety outcomes included anastomotic leak rate and acute kidney injury. Results: A total of 4164 patients were included, with a median age of 68 (i.q.r. 57–75) years (54·9 per cent men). Some 1153 (27·7 per cent) received NSAIDs on postoperative days 1–3, of whom 1061 (92·0 per cent) received non‐selective cyclo‐oxygenase inhibitors. After adjustment for baseline differences, the mean time to gastrointestinal recovery did not differ significantly between patients who received NSAIDs and those who did not (4·6 versus 4·8 days; hazard ratio 1·04, 95 per cent c.i. 0·96 to 1·12; P = 0·360). There were no significant differences in anastomotic leak rate (5·4 versus 4·6 per cent; P = 0·349) or acute kidney injury (14·3 versus 13·8 per cent; P = 0·666) between the groups. Significantly fewer patients receiving NSAIDs required strong opioid analgesia (35·3 versus 56·7 per cent; P < 0·001). Conclusion: NSAIDs did not reduce the time for gastrointestinal recovery after colorectal surgery, but they were safe and associated with reduced postoperative opioid requirement. Abstract : The aim of this study was to assess the role of non‐steroidal anti‐inflammatory drugs (NSAIDs) for reducing ileus after surgery. NSAIDs did not reduce the time for gastrointestinal recovery, but they were safe and associated with reduced postoperative opioid requirement. No effect on ileus, but reduces opioid need A video abstract is available at https://youtu.be/uex40nmCUuU Abstract : Antecedentes: El ileo es frecuente tras cirugía colorrectal electiva y se asocia con un incremento de los eventos adversos y de la duración de la estancia hospitalaria. El objetivo fue evaluar el papel de los fármacos antiinflamatorios no esteroideos ( non‐steroidal anti‐inflammatory drugs, NSAIDs) para reducir el ileo tras la cirugía. Métodos: Estudio de cohortes prospectivo y multicéntrico efecuado por un grupo colaborativo dirigido por estudiantes y cirujanos en formación. Se incluyeron pacientes adultos sometidos a cirugía colorectal electiva entre enero y abril 2018. El resultado primario fue el tiempo hasta la recuperaciòn gastrointestinal, medido por una variable compuesta de función intestinal y tolerancia a la alimentación oral. El impacto de los NSAIDs se exploró utilizando un análisis de regresión de Cox, que incluía los resultados de una encuesta específica dirigida a los centros sobre la adherencia a los principios de la recuperación intensificada. Los resultados secundarios de seguridad incluyeron la dehiscencia anastomótica y la insuficiencia renal aguda. Resultados: Se incluyeron 4.164 pacientes con una mediana de edad de 68 años (rango intercuartílico: 57‐75; 54, 9% varones). Un total de 1.153 (27, 7%) pacientes fueron tratados con NSAIDs en los días postoperarorios 1‐3, de los cuales 1.061 (92, 0%) recibieron inhibidores no selectivos de la ciclooxigenasa. Tras los ajustes por las diferencias basales, el tiempo medio hasta la recuperación gastrointestinal no difería significativamente entre pacientes que recibieron o no recibieron NSAIDs (4, 6 versus 4, 8 días; cociente de riesgos instantáneos, hazard ratio, HR 1, 04, i.c. del 95%: 0, 96‐1, 12, P = 0, 360). No hubo diferencias significativas en la tasa de dehiscencias anastomóticas (5, 4% versus 4, 6%; P = 0, 349) o insuficiencia renal aguda (14, 3% versus 13, 8%; P = 0, 666) entre los grupos. Sin embargo, significativamente menos pacientes de los que recibieron NSAIDs precisaron una analgesia intensa con opioides (35, 3% versus 56, 7%; P < 0, 001). Conclusión: La administración de NSAIDs no redujo el tiempo hasta la recuperación gastrointestinal tras cirugía colorrectal, pero fueron seguros y se asociaron con una reducción en la necesidad de opioides postoperarorios.